MicroCT parameters for multimaterial elements assessment - De Araújo, Olga M. O.; Bastos, Jaqueline Silva [UNESP]; Machado, Alessandra S.; Dos Santos, Thaís M.P.; Ferreira, Cintia G.; Claro, Ana Paula Rosifini Alves [UNESP]; Lopes, Ricardo T. (IOP Publishing, 2018)
Microtomography is a non-destructive testing technique for quantitative and qualitative analysis. The investigation of multimaterial elements with great difference of density can result in artifacts that degrade image quality depending on combination of additional filter. The aim of this study is the selection of parameters most appropriate for analysis of bone tissue with metallic implant. The results show the simulation with MCNPX code for the distribution of energy without additional filter, with use of aluminum, copper and brass filters and their respective reconstructed images showing the importance of the choice of these parameters in image acquisition process on computed microtomography.
Keywords: additional filters; Microtomography; multimaterial elements.